اسلوب القياس المرجعي كألية لتفعيل ادارة التكلفة الاستراتيجية في المؤسسة الاقتصادية دراسة ميدانية بمؤسسة الدهن و مطاحن بلغيث الكبرى ولاية سوق اهراس - سعيدة بوكبوط; خولة قواسمية (My University, 2022)
We aim through this study to know the role of benchmarking method in strategic cost management , as well as how comparative measurement contributes to eveloping the performance and continuity of institution , and this is what led us to , this study concluded the following results The use of benchmarking leads o mproving the efficiency and effectiveness of the performance of the facility, the benchmarking is anintroduction to using the available cost information in anaging and reducing costs The use of the reference method contributes to the development of quantitative and non quantitative reference standards that are inked to the strategic objectives of the institutions , such as reducing costs with the highest levels of quality . the benchmarking method affects the analysis of the atrategic situation and the analysis of cost drivers and value chains , the necessity of the establishments interest in applying the benchmarking method so that the establishment can increase the effectiveness of continuous improvement and increase competitiveness as well as the interest of the establishments in applying the newly developed strategic cost mangement methods Supporting the administration by applying the benchmarking method and allocating material and human resources to implement this method ....................................................... دف من خلال هذه الدراسة إلى معرفة دور أسلوب القياس المرجعي في ادارة التكلفة الاستراتيجية وكذلك كيف شكالية يساهم القياس المقارن في تطوير اداء المؤسسات واستمرارها وهذا ما أدي بنا إلى طرح الا لية : إلى أي : مدى يساهم القياس المرجعي في تفعيل اداء الادارة الاستراتيجية , ولخصت هذه الدراسة الى النتائج التالية ان استخدام المقارنة المرجعية يؤدي إلى تحسين الكفاءة والفعالية لاداء المنشأة وأن المقارنة المرجعية يؤدي هي المت مدخل لاستخدام معلومات التكاليف احة في ادارة وخفض التكلفة , وطذلك استخدام اسلوب القياس المرجعي يساهم في وضع مقاييس مرجعية كمية وغير كمية ترتبط بالاهداف الاستراتيجية للمؤسسات مثل خفض التكلفة مع أعلى مستويات الجودة , يؤثر اسلوب القياس المرجعي في تحليل الموقف الاستراتيجي وتحليل مسببات تكل ال . فة وسلاسل القيمة ضرورة اهتمام المنشات بتطبيق اسلوب القياس المرجعي لكي تتمكن المنشاة من زيادة فاعلية التحسين المستمر وزيادة القدرة التنافسية وكذلك اهتمام المنشات بتطبيق اساليب ادارة التكلفة الاستراتيجية المستحدثة ودعم الادارة بتطبيق أسلوب القياس المرجعي و . تخصيص الموارد المادية والبشرية لتطبيق ا الاسلوب :